2019
DOI: 10.3390/ijerph16122171
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Perceptions of “C.H.A.M.P. Families”: A Parent-Focused Intervention Targeting Paediatric Overweight and Obesity

Abstract: Background: Recently, our team implemented a 13-week group-based intervention for parents of children with obesity (“C.H.A.M.P. Families”). The primary objective of this study was to explore, qualitatively, parents’ perspectives of their experiences in and influence of C.H.A.M.P. Families, as well as their recommendations for future paediatric obesity treatment interventions. Methods: Twelve parents (seven mothers, five fathers/step-fathers) representing seven children (four girls, three boys) with obesity par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Focus groups conducted with parents during the final C.H.A.M.P. Families session revealed that time constraints were perceived as a barrier to health behavior change among participants [61]. Thus, it is possible that the home-based activities were viewed as an additional burden beyond the time commitment already required for the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus groups conducted with parents during the final C.H.A.M.P. Families session revealed that time constraints were perceived as a barrier to health behavior change among participants [61]. Thus, it is possible that the home-based activities were viewed as an additional burden beyond the time commitment already required for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…While C.H.A.M.P. Families was strategically designed as community-based, lifestyle intervention for parents of children with obesity, Reilly and colleagues (2019) noted that some parents who took part in the intervention felt that their children would have benefited from increased participation in the program [61]. Given the ample literature supporting family-based interventions in which parents are the primary agents of change [10][11][12][13][14][15][16][17][18][19][20], establishing a balance between program design and effectiveness/efficacy and participant preferences is imperative.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“… 1 The overweight and obesity in children increased drastically with the most recent estimates that indicate it’s effect in approximately 340 million worldwide. 2 Furthermore, there have been an increasing overweight and obesity in anxious child. 3 The addition of cases overweight and obesity in children occurs in all geographical areas in the world, especially for residents living in urban areas both in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity rates have increased dramatically in school-aged populations [1,2,3,4]. The poor health outcomes associated with obesity usually develop in the later stages of life; however, pathological processes begin in childhood [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The trends for obesity have shown a high prevalence in Hispanic children in the United States. Consequently, the alarmingly high incidence rate of obesity places this population at high risk for developing future health problems such as type 2 diabetes mellitus, dyslipidemia, atherosclerosis, and hypertension [3,4,6].…”
Section: Introductionmentioning
confidence: 99%